2023
DOI: 10.21203/rs.3.rs-2612594/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unmet supportive care needs of patients with breast cancer: A systematic review

Abstract: Background Growing breast cancer patients increases the demand for unmet needs. Few research has focused on any systematic research into unmet need among these groups. This aim is to clarify major elements of unmet needs and factors influencing in order to provide a basis for provision of appropriate medical services. Method A throughout search was conducted in Cochrane Library, PubMed, Embase, Web of Science, Medline from inception through December 2022. Studies investigated unmet supportive care needs of p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 92 publications
0
3
0
Order By: Relevance
“…Many related studies have also been conducted in China, such as a survey in Taiwan on unmet supportive care needs of breast cancer survivors at different phases of cancer or treatment [17] , a research to identify the trajectory patterns and predictors of supportive care needs of elderly breast cancer patients in Shanghai [18] , and a research to investigate the information needs of breast cancer patients in Hong Kong and their satisfaction with the information provided [19] . Patient-reported unmet needs were found to include information needs, psychological/emotional needs, physical/symptoms, medical support, and fear of cancer recurrence/anxiety [20] . However, studies of unmet needs among Chinese breast cancer survivors have only focused on information needs, psychological needs, and total supportive care needs, and have not yet investigated health care needs, and the association of factors such as sleep duration, physical status, and nancial toxicity with unmet needs among Chinese breast cancer patients has not yet been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Many related studies have also been conducted in China, such as a survey in Taiwan on unmet supportive care needs of breast cancer survivors at different phases of cancer or treatment [17] , a research to identify the trajectory patterns and predictors of supportive care needs of elderly breast cancer patients in Shanghai [18] , and a research to investigate the information needs of breast cancer patients in Hong Kong and their satisfaction with the information provided [19] . Patient-reported unmet needs were found to include information needs, psychological/emotional needs, physical/symptoms, medical support, and fear of cancer recurrence/anxiety [20] . However, studies of unmet needs among Chinese breast cancer survivors have only focused on information needs, psychological needs, and total supportive care needs, and have not yet investigated health care needs, and the association of factors such as sleep duration, physical status, and nancial toxicity with unmet needs among Chinese breast cancer patients has not yet been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…A scoping review is recommended to comprehensively assess the breadth of the research topic and identify gaps worthy of further investigation (Pollock et al., 2021; Tricco et al., 2016). Several reviews have been conducted on this topic (Fan et al., 2023; Fiszer et al., 2014; Khajoei et al., 2023; Wabula et al., 2020). A systematic review of 23 quantitative studies examined the prevalence and factors associated with unmet care needs in women with breast cancer (Fiszer et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, these reviews did not show the research advancements and identified gaps that warrant further investigation. Moreover, a recent scoping review synthesized the evidence related to the unmet care needs of adults with breast cancer (Fan et al., 2023). This review included breast cancer survivors regardless of cancer treatment and disease stage.…”
Section: Introductionmentioning
confidence: 99%